Employing Self and Peer Editing Techniques to Teach Writing Recount Texts for Students with High and Low Motivation (The Case of Grade 5 of Mondial Primary School in the Academic Year of 2015/2016) - Ardy Prabasiwi, Evita; Warsono, Warsono (English Education Journal, 2017)
This current study aims at exploring the effect of self-editing technique and peer editing technique for teaching recount text writing to students with high and low motivation and explaining whether there is significant interaction among teaching technique, writing skill, and studentsâ motivation. This study is an experimental research with a 2 x 2 factorial design. Respectively, the results of the present study have revealed that firstly, there is no significant difference between pretest and posttest result of students with high motivation students that are treated with self-editing technique. Secondly, there is significant difference of pretest and posttest scores of low-motivated students who are treated by self-editing technique. Thirdly, it is described that peer editing technique has significant effect to be treated to students with high motivation in improving the writing skill of recount text. Fourthly, peer editing technique is not effective to be applied for low-motivated students because there is no significant difference between pretest and posttest scores of low-motivated students treated by peer editing technique. Fifthly, there is no difference in the improvement between students with high and low motivation in writing recount texts through peer and self-editing technique. The summary of the analysis shows that both techniques, peer and self-editing techniques are applicable to treat high and low-motivated students in teaching recount texts writing.